Public awareness in Wales of the UK Yellow Card scheme for reporting suspected adverse drug reactions. Issue 8 (19th January 2021) - Bracchi, Robert C.; Tseliou, Foteini; Copeland, Lauren; Routledge, Philip A.; Thomas, Alison; Woods, Fiona; Adams, Alana; Walker, Jenna; Jadeja, Mitul; Atkinson, Mark D.; Ashfield‐Watt, Pauline
Abstract : We used the HealthWise Wales (HWW) platform to explore public knowledge about the UK Yellow Card scheme (YCS), the spontaneous reporting scheme for suspected adverse drug reactions (ADRs) and whether a short information video could improve awareness. Members of the public in Wales ( n = 1606) completed a questionnaire about the YCS, watched the information video and then completed a follow‐up questionnaire. Almost half (46.5%) of respondents said they had previously experienced an ADR (>90% of the ADRs involving prescribed medicines). Before the video, 18% of respondents knew how to report an ADR via the YCS and of these, 34% were from allied‐health professions. Immediately after watching it, 71% participants reported knowing how to report and 82% reported being confident to report. If this awareness were maintained, such an approach could contribute to improved reporting of suspected ADRs by the public.